PCs für Dummies ruck, zuck - Muir, Nancy 1954- (Wiley-VCH, 2011)
Annotation
"Wir machen alles leichter"--Cover. - Originally published in English as: PCs just the steps for dummies by Wiley Pub. 2009. - Includes index. - Print version record
Keywords: Microcomputers; Micro-ordinateurs; microcomputers